The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Presses universitaires de Lyon, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''– Fourni par l'éditeur.
Le texte Lavigne, J. (2017). Autopornography and the struggle for the recognition of a sexual subjectivity: a theoretical analysis from Loree Erickson's testimony a été donné en lecture au cours SEX1920
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie